2008
DOI: 10.1186/1471-2199-9-51
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and expression patterns of a membrane-bound trehalase from Spodoptera exigua

Abstract: Background: The chitin biosynthesis pathway starts with trehalose in insects and the main functions of trehalases are hydrolysis of trehalose to glucose. Although insects possess two types, soluble trehalase (Tre-1) and membrane-bound trehalase (Tre-2), very little is known about Tre-2 and the difference in function between Tre-1 and Tre-2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
110
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 89 publications
(115 citation statements)
references
References 41 publications
5
110
0
Order By: Relevance
“…Trehalase catalyzes the conversion of the disaccharide trehalose into two glucose monomers. Two types of trehalases (soluble and membrane bound) are encoded in the S. exigua genome; the membrane-bound trehalase has been characterized in the midgut and fat body (Tang et al, 2008). The slight decrease of trehalose titer in the hemolymph of S. exigua in the current study may have been induced by the shutdown of trehalose biosynthesis in fat body as well as by the continuous usage by peripheral tissues.…”
Section: Discussionmentioning
confidence: 79%
“…Trehalase catalyzes the conversion of the disaccharide trehalose into two glucose monomers. Two types of trehalases (soluble and membrane bound) are encoded in the S. exigua genome; the membrane-bound trehalase has been characterized in the midgut and fat body (Tang et al, 2008). The slight decrease of trehalose titer in the hemolymph of S. exigua in the current study may have been induced by the shutdown of trehalose biosynthesis in fat body as well as by the continuous usage by peripheral tissues.…”
Section: Discussionmentioning
confidence: 79%
“…Trehalase (encoded by 2 genes, Treh1 and Treh2) is an anomer-inverting α-trehalose-1-D-glucosidase, which plays an important role in the use of carbohydrates by hydrolyzing trehalose molecules into 2 glucose molecules (Tang et al, 2008). To date, 2 forms of trehalase have been found and cloned in several insect species (Wyatt, 1967), including Apis mellifera (Lee et al, 2007), Bombyx mori (Mitsumasu et al, 2005), Omphisa fuscidentalis (Tatun et al, 2008), Pimpla hypochondriaca (Parkinson et al, 2003), Spodoptera exigua (Tang et al, 2008), and Tenebrio molitor (Takiguchi et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…To date, 2 forms of trehalase have been found and cloned in several insect species (Wyatt, 1967), including Apis mellifera (Lee et al, 2007), Bombyx mori (Mitsumasu et al, 2005), Omphisa fuscidentalis (Tatun et al, 2008), Pimpla hypochondriaca (Parkinson et al, 2003), Spodoptera exigua (Tang et al, 2008), and Tenebrio molitor (Takiguchi et al, 1992). Initial studies of trehalose and protein purification have found that the main distribution of soluble trehalase (Treh1) and membrane-bound trehalase (Treh2) sometimes differed (Tang et al, 2008), which might indicate different functions.…”
Section: Introductionmentioning
confidence: 99%
“…Membranes were prehybridized at 42°C for 4 h and then incubated with the -32 Plabelled CpiTPS probe (same probe as described for Southern blotting) at 42°C for 18 h in 5× SSPE containing 50% formamide, 5× Denhardt's solution, 0.1% SDS, and 100 mg/ml salmon sperm DNA. After hybridization, the membrane was washed with 0.2× SSPE at 45°C, and exposed to X-ray film at -70°C for 24 h (Choo et al, 2007;Tang et al, 2008).…”
Section: Northern Blot and Rt-pcr Analysismentioning
confidence: 99%
“…It is synthesized mainly by the fat body (an organ analogous in function to a combination of the liver and adipose tissue in vertebrates) and is released rapidly into the hemolymph and other tissues in larvae, pupae, and adults (Candy & Kilby, 1959, 1961Elbein, 1974;Becker et al, 1996;Tang et al, 2008). It is reported that trehalose is synthesized from glucose phosphate.…”
Section: Introductionmentioning
confidence: 99%